Impact of Feeding Cover Crop Forage Containing Brassicas to Steers during Backgrounding on Palatability Attributes of Beef Strip Steaks - Christina Bakker; Lydia Hite; Cody Wright; Alexander Smart; Thu Dinh; Amanda Blair; Keith Underwood; J. Kyle Grubbs (Foods, 2021)
Brassica cover crops have been widely used for improving soil health and as a feed resource for grazing cows, but their use in backgrounding diets is unknown. The objective of this study was to determine the impact of feeding a brassica cover crop mixture during backgrounding on beef palatability. Thirty steers were assigned to one of two dietary treatments during backgrounding with (1) ad libitum access to freshly cut brassica cover crop forage (CC) containing radish, turnip, rapeseed, and rye grass, or (2) common Midwestern dry lot backgrounding diet (CON). The steers were transitioned to a common finishing diet after backgrounding. Striploins were collected after harvest, and were analyzed for evaluation of the Warner–Bratzler shear force (WBSF), collagen content, autolysis of calpain-1, proteolysis of desmin, and troponin-T; in addition, the tenderness, juiciness, and flavor evaluated by a trained sensory panel. A treatment x day interaction was observed for WBSF (p = 0.02). Steaks from the CON diet were less tender than CC steaks on days 3 and 7, but did not differ on days 14 and 21. Feeding a brassica mixture cover crop during the backgrounding phase of production did not impact the collagen content, autolysis of calpain-1, or proteolysis of desmin and troponin-T. Thus, additional investigation into the mechanisms responsible for the differences observed in instrumental tenderness is warranted.